Coarse Examples of Baues Cofibration Category - Mohamad, Nadia E. Gheith; Mitchener, Paul D. (Sarajevo Journal of Mathematics, 2022)
In this article, we set up a framework for homotopy theory in coarse geometry by defining a notion of cofibration for coarse maps. We show that the axioms of a Baues cofibration category hold.